Linkage measures of the real estate sector considering the effect of capital - Song, Yu; Liu, Chunlu; Langston, Craig (International Journal of Strategic Property Management, 2010)
A significant limitation in previous linkage relevant research is that the flow of capital goods is not addressed. Using the OECD input‐output tables, this research first generates a new input‐output model considering capital as an intermediate factor. Using the new model, the real estate linkages are re‐calculated and investigated in order to evaluate appropriately the impact of the real estate sector on national economies. The findings verify that the linkages of the real estate sector were extremely underestimated in previous research. A correct linkage measure of the real estate sector can contribute to produce correct information corresponding to the sectors responsible for the economic growth during the period under study and provide substantial contributions towards guiding the appropriate strategies for future economic development.First Published online: 18 Oct 2010